Assessing streamflow forecast accuracy for flash flood events in Puerto Rico - Gerardo Trossi-Torres; Jonathan Muñoz-Barreto; Alesandra C. Morales-Vélez; Ernesto Rodriguez-Fernández; Odalys Martínez-Sánchez; Tarendra Lakhankar (Journal of Hydrology: Regional Studies, 2024)
Study region: Puerto Rico. Study focus: A comprehensive understanding of the hydrological cycle is crucial, where models play a key role in monitoring and predicting flood events, enabling better analysis of event behavior. This study evaluated the National Water Model version 2.1, currently operated and monitored by the National Oceanic and Atmospheric Administration. The study focused on assessing the model's ability to produce reliable streamflow forecasts in Puerto Rico, which was recently added to the model in 2021. The evaluation was conducted with five significant rainfall events, including four flash floods and one hurricane in 2022. The forecasted streamflow was determined using 83 river gauge measured data across Puerto Rico during each event. New hydrological insights for the region: Based on the assessment conducted for the NWM in Puerto Rico, the model has the ability to produce streamflow forecasts and obtain correct trends, only in some cases. The model's accuracy and precision are limited to the forcing supplied during its operation. The model performs optimally in conditions where rainfall forcing is similar to observed, and deviations lead to an unreliable forecast. This study established the primary concern for making a reliable forecast is the forcing supplied. The currently operating model produces overestimated or underestimated forecasts with minimal close estimates, but its outputs can still always provide a general idea of streamflow activity across the island.